Travellers' knowledge, attitudes and practices prevention of infectious diseases: a cross sectional study - Chow, Zhen Yee; Ching, Siew Mooi; Ramachandran, Vasudevan; Hoo, Fankee; Wan Sulaiman, Wan Aliaa; Foo, Yoke Loong; Tey, Yin Yee; Liong, Chang Wing; Wen, Lim Hui; Han, Tan Chun (Seameo Regional Tropical Medicine & Public Health, 2018)
International travel is common, increasing the risk for travel related infections, making it important to understand the knowledge, attitudes and practices (KAP) of international travellers regarding prevention of travel related illnesses. We aimed to determine the KAP of travellers at two Malaysian airports, in order to inform traveller health programs. We conducted face to face interviews with travellers at Kuala Lumpur International Airport and Sultan Abdul Aziz Shah Airport, Malaysia in 2014. Study subjects were selected via convenient sampling. Inclusion criteria were travellers aged ≥18 years who were departing from the studied airports, were able and willing to participate in the study. Subjects were asked about their KAP regarding various travel health subjects. The data from these interviews were collected, summarized and examined with SPSS version 21 and multiple logistic regression analysis to determine factors associated with poor KAP regarding travel health. A total of 316 subjects were included in the study; 57.6% were male and 55.4% were Malaysians. Forty point five percent of subjects sought pre-travel health advice. Of those who sought pre-travel health advice, 39.8% sought it from family or friends, 35.2% from the internet and 12.5% from a physicians. Fifty-two point eight percent of subjects had received pre-travel vaccinations. No subjects were traveling to a malaria high risk country as determined by the Centers for Disease Control and Prevention, 8.2% were travelling to a moderate risk country, 28.9% were travelling to a low risk country, 12.0% were travelling to a very low risk country and 50.9% were travelling to a country with no malaria risk. Four point one percent of subjects took malaria prophylaxis medication. On multivariate logistic regression analysis, the older the study subject age, the better the travel health knowledge [odds ratio (OR)=1.03; 95% confidence interval (CI): 1.01-1.05; p = 0.009]. Being female (OR: 1.92; 95%CI: 1.16-3.18; p = 0.011) and those who sought travel health advice (OR: 1.77; 95%CI: 1.06-2.95; p = 0.028) were more likely to have good practice on travel health. Therefore, awareness program should target the male travellers to improve health practices.